Green Toxicology : Know Early About and Avoid Toxic Product Liabilities - Maertens, Alexandra; Hartung, Thomas (My University, 2018)
Toxicology uniquely among the life sciences relies largely on methods which are more than 40-years old. Over the last 3 decades with more or less success some additions to and few replacements in this toolbox took place, mainly as alternatives to animal testing. The acceptance of such new approaches faces the needs of formal validation and the conservative attitude toward change in safety assessments. Only recently, there is growing awareness that the same alternative methods, especially in silico and in vitro tools can also much earlier and before validation inform decision-taking in the product life cycle. As similar thoughts developed in the context of Green Chemistry, the term of Green Toxicology was coined to describe this change in approach. Here, the current developments in the alternative field, especially computational and more organo-typic cell cultures are reviewed, as they lend themselves to front-loaded chemical safety assessments. The initiatives of the Center for Alternatives to Animal Testing Green Toxicology Collaboration are presented. They aim first of all for forming a community to promote this concept and then for a cultural change in companies with the necessary training of chemists, product stewards and later regulators.
Keywords: 570